The Lives of Intersex People: Socio-Economic and Health Disparities in Mexico - Ercio A. Mu\~noz; Melanie Saavedra; Dario Sansone (Institute of Labor Economics (IZA), 2024)
This paper reports socio-economic and health outcomes for intersex people in Mexico using data collected between 2021 and 2022. This is the first study relying on a large nationally representative survey including information on sex variations to document substantial negative outcomes for intersex individuals. Around 1.6% of individuals aged 15-64 are intersex. There are significant disparities in mental, physical, and sexual health when comparing intersex individuals to the general population, including higher rates of bullying, stigmatization, harassment, and violence throughout the life cycle, as well as higher rates of suicidal intention. Additionally, intersex individuals have lower education levels and face substantial barriers in the workplace and healthcare environments.
Keywords: I14; J15; J16; J71; 330; intersex; stigma; suicide; Mexico; LGBTQ+